Pulse Oximeter Portable - I Putu Anna Andika; Triana Rahmawati; M. Ridha Mak’ruf (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2019)
Pulse oximeter is a tool to monitor oxygen saturation in the blood (arteries) and also a person's heart rate (BPM) without having to go through blood analysis. Lack or excess of oxygen in the blood will cause illness and disruption of the body's work. At a certain level, this disease can cause the risk of death. The purpose of this study was to develop a pulse oximeter. The design of this equipment uses the MAX30102 sensor. Then the sensor will start working and Arduino will do data processing. Data from the MAX30102 sensor entering the I2C pin is then displayed on the TFT LCD screen. This equipment is made portable to make it easier for users to do monitoring anytime and anywhere.This test is done by comparing modules with standard measuring instruments. From the results obtained, this equipment is worthy of use because by